Micrometeorological assessment of sensitivity of canopy resistance to vapour pressure deficit in a Mediterranean oak forest - Pitacco, A; Gallinaro, N (Ann. For. Sci., 1996)
Canopy surface resistance to water vapour (rc) of an extensive Quercus ilex L stand (Bosco Mesola, northeast Italy) has been evaluated by inverting the Penman-Monteith equation. The latent heat flux was estimated by applying the Bowen ratio-energy budget micrometeorological method. A linear relationship was found between rc and the vapour pressure deficit. Canopy resistance increased regularly during the day and that yielded a recurring diurnal pattern of energy partitioning where most of the latent heat was dissipated in the early morning and the release of sensible heat increased after midday. This behaviour has been confirmed also by independent estimates of transpiration, based on measurements of sap flow velocity in small branches. Ecological consequences of this feature are briefly discussed applying the concept of coupling between canopy and atmosphere
Keywords: canopy resistance; energy balance; Evapotranspiration; Quercus ilex L; sap flow

Evaluation of actual evapotranspiration of a Quercus ilex L. stand by the Bowen ratio-energy budget method - Pitacco, A; Gallinaro, N; Giulivo, C (Plant Ecology, 1992)
Actual evapotranspiration from a closed-canopy Quercus ilex L. stand has been estimated by applying the Bowen Ratio-Energy Budget method. Daily water loss was 3.5 mm day ~, with a peak rate near 0.6 mm hour ~. The phenomenon of thermal inversion, quite common in mediterranean climates, seemed to play a significant role in reducing evapotranspiration, by promoting dew formation and delaying the establishment of fluxes of latent and sensible heat away from the canopy. Dew, which may form over many hours in the night, appears to be a major sink of available energy in the early morning and may represent a useful water source for stressed foliage. The alternating processes of condensation and evaporation may have a beneficial effect on the closed stand micro-environment.
Keywords: actual evapotranspiration; bowen ratio; energy balance; Quercus ilex L